PERANAN PEMBIAYAAN BAITUL MAL WAT (BMT) AGAM MADANI TERHADAP PERKEMBANGAN UMKM DI KENAGARIAN PAKAN SINAYAN - Syafira rahmi; Santi Deswita; Awaluddin, Habibatur Ridhah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Due to the high interest rates and pressing requirements, lower-class people still have trouble accessing banking institutions, especially Islamic banking, and raising their business capital by taking out loans from loan sharks. Low-quality human resources and capital stock are the issues MSMEs face. Finding out how BMT Agam Madani finance contributes to the growth of MSMEs in Kenagarian Pakan Sinayan is the goal of this study. The approach is qualitative descriptive, specifically utilising documentation and interviewing approaches. The results of the study indicate that BMT Agam Madani has played a role in the development of MSMEs by providing capital financing and providing guidance to customers. Although there are still challenges in the development of mico business such as the existence of congestion in payments and the lack of public knowledge in transactions. The conclusion of this study is the importance of BMT Agam Madani providing guidance to MSMEs in order to smooth financing payments and facilitate the business being run.